Persamaan Antara Perkuliahan Berbasis Penelitian dengan Pendidikan STEM - Lukman Hadi; Ahmad Mudzakir; Yuli Rahmawati; Asep Kadarohman (Jurnal Penelitian Pendidikan IPA, 2025)
STEM education has transitioned from a model characterized by passive learning and strict laboratory exercises to one focused on active inquiry, student autonomy, and research involvement. Central to this educational transformation are Course-Based Undergraduate Research Experiences (CUREs), which integrate genuine research into the curriculum. This review synthesizes 15 current studies from Scopus to examine the common focus between cures and STEM education. CUREs and reformed STEM pedagogies integrate authentic scientific practice, student-centered learning, and inclusive access to improve persistence, equity, and workforce readiness. By embedding research with uncertain outcomes into coursework, these approaches broaden participation, remove barriers, and build critical thinking, problem-solving, and communication skills. They also enhance scientific identity and self-efficacy, particularly for underrepresented students, supporting retention and success in STEM. Scalable and supported by national initiatives, CUREs show that high-impact, research-rich learning can be delivered widely without losing depth, preparing a skilled and diverse scientific community for complex challenges.